2001
DOI: 10.1053/rmed.2001.1180
|View full text |Cite
|
Sign up to set email alerts
|

Hospital re-admission in patients with acute exacerbation of chronic obstructive pulmonary disease

Abstract: A retrospective study was carried out in a Hong Kong regional hospital with 24-h emergency service, to study the factors associated with shorter time to re-admission after acute exacerbation of chronic obstructive pulmonary disease (COPD). From 1 January 1997 to 31 December 1997, the first admission (index admission) of each patient through the emergency room with COPD/chronic bronchitis/emphysema was included. A total of 551 patients fulfilled the inclusion criteria. The total acute and rehabilitative length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 21 publications
5
58
0
Order By: Relevance
“…Many disease-specific models fail to account for the multiple comorbidity often witnessed in hospitalized general medical patients. [13][14][15][16][17][18][19][20][21] It is fortunate that increased hospitalization and lengthy hospital stays are useful proxies for disease severity and multiple comorbidities, which are more difficult to quantify.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many disease-specific models fail to account for the multiple comorbidity often witnessed in hospitalized general medical patients. [13][14][15][16][17][18][19][20][21] It is fortunate that increased hospitalization and lengthy hospital stays are useful proxies for disease severity and multiple comorbidities, which are more difficult to quantify.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies looking at hospital readmissions are disease specific. [13][14][15][16][17][18][19][20][21] There are relatively few studies examining the risk factors for readmission among all primary care patients, and many of these were performed outside the United States or in hospitalist practices. 10,[22][23][24][25] It is well known that a small proportion of patients account for a disproportionate number of hospital admissions and health care costs.…”
mentioning
confidence: 99%
“…A retrospective study from Hong Kong on 551 patients showed a 59.35% re-admission rate after 12 months [28]. In the prospective EFRAM study, 63% of 340 patients were readmitted during the 1yr follow-up time [4].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] However, these studies included patients with compensated respiratory acidosis and decompensated respiratory acidosis, which was aforesaid found to be a poor prognostic factor. Some respirologists believe that the absolute value of PaCO2 is not as critical as the pH, with the latter being a better predictor of disease severity as it reflects the magnitude and changes of PaCO2.…”
Section: Introductionmentioning
confidence: 99%